Efektivitas Asam Glutamat Sebagai Inhibitor Korosi pada Baja Karbon dalam Larutan NaCl 1% - Ni Ketut Ketis; Deana Wahyuningrum; Sadijah Achmad; Bunbun Bundjali (Institut Teknologi Bandung, 2010)
Corrosion towards the inner parts of oilfield pipelines is one of most disturbing problems in oil and gas industries. Amino acid and its derivatives have potent as corrosion inhibitor, including glutamic acid, which has been studied within this research project. The effectivity of glutamic acid as corrosion inhibitor towards carbon steel in 1% (w/v) NaCl solution saturated by CO2 has been determined utilizing Tafel method with the optimization of glutamic acid concentration, pH, and temperature of tested medium. Glutamic acid showed the highest corrosion inhibition efficiency at room temperature (26oC), which is 48.19% at the concentration of 8 ppm in 1% NaCl solution and pH 6.5. The presence of acetate buffer solution in the medium that was being tested and at the temperature higher than room temperature has caused glutamic acid at the concentration of 8 ppm became ineffective to be applied as corrosion inhibitor.